Impact of clomazone on bacterial communities in two soils - He, Hairong; Huang, Jiarui; Zhao, Zhenzhu; Feng, Weisheng; Zheng, Xiaoke; Du, Pengqiang (Frontiers in Microbiology, 2023)
Introduction Bacterial communities are important for soil functions, but the effect of clomazone on network complexity, composition, and stability is not well studied. Method In this study, two agricultural soils were used to test the impact of clomazone on bacterial communities, and the two soils were treated with three concentrations of clomazone (0, 0.8, 8, and 80 mg kg1) in an incubator. Results and discussion Bacterial network nodes, links, and average degrees were all decreased by 9–384, 648–829, and 0.703–2.429, respectively. Based on keystone nodes, the topological roles of the nodes were also influenced by clomazone. Bacterial network composition was also impacted based on the analysis of similarity (ANOSIM) and network dissimilarity. Compared with control and clomazone treatments in both soils, the ANOSIM between control and all clomazone treatments was higher than 0.6, network dissimilarities were 0.97–0.98, shared nodes were 131–260, and shared links were 12–100. The bacterial network stability was decreased by clomazone, with decreased robustness by 0.01–0.016 and increased vulnerability by 0.00023–0.00147 in both soils. There were fewer bacterial network modules preserved after clomazone treatment, and the bacterial network community functions were also impacted in both soils. Based on these results, soil bacterial species connections, modularization, and network stability were significantly impacted by clomazone.